Spatiotemporal Profiles of Proprioception Processed by the Masseter Muscle Spindles in Rat Cerebral Cortex: An Optical Imaging Study - Fujita, Satoshi; Kaneko, Mari; Nakamura, Hiroko; Kobayashi, Masayuki (Frontiers in Neural Circuits, 2017)
Muscle spindles in the jaw-closing muscles, which are innervated by trigeminal mesencephalic neurons (MesV neurons), control the strength of occlusion and the position of the mandible. The mechanisms underlying cortical processing of proprioceptive information are critical to understanding how sensory information from the masticatory muscles regulates orofacial motor function. However, these mechanisms are mostly unknown. The present study aimed to identify the regions that process proprioception of the jaw-closing muscles using in vivo optical imaging with a voltage-sensitive dye in rats under urethane anesthesia. First, jaw opening that was produced by mechanically pulling down the mandible evoked an optical response, which reflects neural excitation, in two cortical regions: the most rostroventral part of the primary somatosensory cortex (S1) and the border between the ventral part of the secondary somatosensory cortex (S2) and the insular oral region (IOR). The kinetics of the optical signal, including the latency, amplitude, rise time and decay time, and half duration, in the S1 region for the response with the largest amplitude were comparable to those in the region with the largest response in S2/IOR. Second, we visualized the regions responding to electrical stimulation of the masseter nerve, which activates both motor efferent fibers and somatosensory afferent fibers, including those that transmit nociceptive and proprioceptive information. Masseter nerve stimulation initially excited the rostral part of the S2/IOR region, and an adjacent region responded to jaw opening. The caudal part of the region showing the maximum response overlapped with the region responding to jaw opening, whereas the rostral part overlapped with the region responding to electrical stimulation of the maxillary and mandibular molar pulps. These findings suggest that proprioception of the masseter is processed in S1 and S2/IOR. Other sensory information, such as nociception, is processed in a region that is adjacent to these pulpal regions and is located in the rostral part of S2/IOR, which receives nociceptive inputs from the molar pulps. The spatial proximity of these regions may be associated with the mechanisms by which masseter muscle pain is incorrectly perceived as dental pain.